Results of the international language and literature competition for gifted youth of Ukraine - Sharova, Tetiana; Safonov, Yuriy; Sharov, Sergii; Zemlianska, Alina (International Journal of Evaluation and Research in Education (IJERE), 2024)
The article provides the analysis of the results of the Taras Shevchenko International Language and Literature Competition for Pupils and Student Youth in 2018-2022. The methods of the quantitative analysis were used to determine the number of participants and winners of the competition (diplomas of I, II, and III degree) in each region of Ukraine, as well as among the foreign participants. It was found that over the past 5 years, 3,384 people from 24 regions of Ukraine and the city of Kyiv participated in the language and literature competition. The winners were 1,636 people, which is 48.3% of the total number of participants. It was found that 240 participants from 16 countries around the world took part in the competition. The obtained results will allow us to identify the regions of Ukraine and its international partners who actively participated in the competition; Departments of Education and Science of Ukraine will be able to popularize the Ukrainian language and enhance the involvement of gifted youth in intellectual competitions. The further research will provide the quantitative analysis of participants who are going to take part in All-Ukrainian competitions in 2023-2024 academic years.